Cognitive, affective and behaviour outcomes of a safety training program - Duarte, L.; Olea, S. A.; Silva, S. A. (European Safety and Reliability Conference: Advances in Safety, Reliability and Risk Management, ESREL 2011, 2012)
Safety training is a key intervention strategy for developing systems, methods and actions that allow more and better safety performance and contributes for changing or developing organizations safety culture. The study was conducted in four phases: 1) initial assessment conducted 15 days prior to training (covering safety perceptions, attitudes and behaviours); 2) evaluation of safety knowledge one hour before the start of training; 3) assessment of safety knowledge 1 hour after training; 4) final evaluation of safety perceptions, attitudes and behaviours, six months after training. A total of 330 workers from a non-profit institution participated in this study pre and post test phases. Results of paired T-test analysis show statistical significant differences for all variables in this study revealing a positive increase after training.